2021
DOI: 10.3390/ani11092584
|View full text |Cite
|
Sign up to set email alerts
|

Successful and Unsuccessful Brain Aging in Pets: Pathophysiological Mechanisms behind Clinical Signs and Potential Benefits from Palmitoylethanolamide Nutritional Intervention

Abstract: Canine and feline cognitive dysfunction syndrome is a common neurodegenerative disorder of old age and a natural model of human Alzheimer’s disease. With the unavoidable expanding life expectancy, an increasing number of small animals will be affected. Although there is no cure, early detection and intervention are vitally important to delay cognitive decline. Knowledge of cellular and molecular mechanisms underlying disease onset and progression is an equally decisive factor for developing effective approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 256 publications
(363 reference statements)
0
6
0
Order By: Relevance
“…Although studies in small animals are still scarce, there is growing evidence that endocannabinoid-like ALIAmides play key roles in the health of different body organs, such as the gastrointestinal tract [ 113 , 114 ] and the nervous system [ 32 , 34 , 37 ], as well as the upper and lower urinary tract [ 115 , 116 , 117 , 118 ] and the musculoskeletal system [ 97 , 119 , 120 ]. In addition, the deep involvement of ALIAmides in obesity-induced metainflammation is becoming increasingly evident [ 69 , 113 , 121 , 122 , 123 ].…”
Section: Preclinical and Clinical Results In Small Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies in small animals are still scarce, there is growing evidence that endocannabinoid-like ALIAmides play key roles in the health of different body organs, such as the gastrointestinal tract [ 113 , 114 ] and the nervous system [ 32 , 34 , 37 ], as well as the upper and lower urinary tract [ 115 , 116 , 117 , 118 ] and the musculoskeletal system [ 97 , 119 , 120 ]. In addition, the deep involvement of ALIAmides in obesity-induced metainflammation is becoming increasingly evident [ 69 , 113 , 121 , 122 , 123 ].…”
Section: Preclinical and Clinical Results In Small Animalsmentioning
confidence: 99%
“…A large body of evidence has been accumulating on the prohomeostatic functions of ALIAmides in several diseases sustained by non-resolving inflammatory and neuroinflammatory responses. The findings have been reviewed by several excellent papers, to which the reader is encouraged to refer [ 3 , 32 , 33 , 34 , 35 , 36 , 37 ]. After addressing a few general key points on ALIAmides, here we will focus exclusively on the main studies performed on small animals.…”
Section: Introductionmentioning
confidence: 99%
“…Some important pharmaceutical compounds such as cardol, 2‐hydroxy‐gamma‐butyrolactone, 3‐furanmethanol, meglumine, cyclopropyl carbinol, palmidrol, and resorcinol were identified in the raw and cooked pasta samples (Table 1) indicating the medicinal properties of the enriched pasta. Cardol, for example, has been reported as an antifilarial metabolite in cashew ( Anacardium occidentale ) (Suresh & Raj, 1990), while palmidrol also known as palmitoylethanolamide has been shown to play a role in exerting neuroprotection and rebalancing neuroinflammation in animals (Scuderi & Golini, 2021). More recently, some authors demonstrated that palmidrol could function as a natural neuroprotector against COVID‐19 inflammation in humans (Roncati et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…We’ve reported that gut-microbiome active dietary interventions (e.g., resistant starch) can also modulate circulating status of endocannabinoids and N-acylated amino acids in cats [ 19 ]. Since these signaling lipids play important roles in feline physiology [ 46 , 47 , 48 , 49 , 50 ] and increasing evidence indicates they are subject to nutritional modulation [ 48 , 49 ], the current report will aid in determining feline dietary interventions which are appropriate for lifestage or health status that can be benefitted by changes in endocannabinoid and N-acylated amino acid status.…”
Section: Discussionmentioning
confidence: 99%